The Effect of The Addition of Papaya Puree on The Chemical and Organoleptic Properties of Pineapple Jam - Rizky Jamaluddin; Meitycorfrida Mailoa; Priscilia Picauly (Universitas Pattimura, 2022)
based on its chemical and sensory properties. A completely randomized experimental design was applied in this study with 4 levels of treatment, namely 0%, 10%, 20%, and 30%, replicated twice. Moisture content, vitamin C content, total dissolved solids, and total acidity were measured, followed by sensory analysis. Sensory analysis was carried out using hedonic tests and descriptive hedonic qualities, which included color, taste, texture, and overall. The treatment of adding 20% papaya to jam was found to have the best chemical characteristics, namely 41.4% moisture content, 0.07% vitamin C,54.65% total soluble solids, and 1.54% total acidity. The jam with 20% papaya puree was liked for its color (3.3), taste (3.3), texture (3.1), and overall rating of (3.3) like. The jam was perceived to have an orange color (2.7), a slightly pineapple taste (2.5), and a slightly soft texture (2.9).